Assessment of English Language Teaching for 21st Century: Teachers’ Perspectives on Traditional and Alternative Assessment - Fadilah, Rahmi; Ayudhia, Honesty Yonanda; Chairani, Vici Syahril; Afni, Fauza (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2023)
There is a debatable issue about the use of traditional and alternative assessment in ELT in the 21st century. The issue comes from the effectiveness of using traditional and alternative assessment to help teacher to assess the students in classroom situations in ELT. The problem is the teachers do not have better perspective in the challenges of assessment of ELT in the 21st century through alternative assessment or using both traditional and alternative assessment in classroom situation. That problem makes the use of assessment is not really effective to assess specific skill (listening, reading, writing, and speaking) of the students. This study aims, therefore, to investigate teachers’ perspective on the use of traditional and alternative assessment in ELT. The methodology of the research is using survey research with fifty English teachers as samples of this research. The data was collected by using questionnaire combine with open-ended questions relate with teachers’ perspective on traditional and alternative assessment. The results show that many teachers are really comfort with traditional assessment rather than alternative assessment since they claimed that traditional assessment is easier and more familiar to conduct in classroom situation. However, those perspectives have to be changed, the teacher should use both traditional and alternative assessment based on appropriate purposes and skills because there are challenges in assessment of ELT in 21st century to make the assessment process become more effective to improve students’ performance in English. It will be helpful by knowing the advantages and disadvantages of using traditional and alternative assessment in classroom situation to help the teacher to use them balance in the teaching and learning process.